Hubungan Self Efficacy dengan Pengambilan Keputusan Karir Mahasiswa UIN Sjech M. Djamil Djambek Bukittinggi - Chandra Ayu Ningrum; Alfi Rahmi; Fadhilla Yusri; Muhiddinur Kamal (YASIN, 2026)
Although career decision-making is an important aspect of student development, many students still experience difficulty determining their career direction and choices due to low self-efficacy. This condition is indicated by weak confidence in their own abilities, limited understanding of appropriate potential and employment opportunities, and hesitation in making career decisions. This study aims to determine the relationship between self-efficacy and career decision-making among students of the 2022 cohort of Guidance and Counseling at UIN Sjech M. Djamil Djambek Bukittinggi. This study used a quantitative approach with a correlational method. The research population consisted of Guidance and Counseling students from the 2022 cohort, with a sample of 113 students. Data were collected using a self-efficacy questionnaire and a career decision-making questionnaire whose validity and reliability had been tested. The data were analyzed using the Pearson Product Moment correlation test. The results showed a significant positive relationship between self-efficacy and career decision-making, with a significance value of 0.010 < 0.05 and a correlation coefficient of 0.635. This value indicates a strong level of relationship based on the correlation coefficient range of 0.60–0.799. These findings affirm that the higher students’ self-efficacy, the better their ability to make career decisions that align with their potential, abilities, and life goals. The conclusion of this study shows that self-efficacy is an important psychological factor in students’ career decision-making process. The implications of this study emphasize the need to strengthen career guidance and counseling services in higher education through programs for developing self-confidence, exploring potential, and providing systematic career planning assistance.